Strengthening public health education in population and reproductive health through an innovative academic partnership in Africa: The gates partners experience - Oni, G.; Fatusi, A.; Tsui, A.; Enquselassie, F.; Ojengbede, O.; Agbenyega, T.; Quakyi, I.A. (Global Public Health, 2011)
Poor reproductive health constitutes one of the leading public health problems in the world, particularly in sub-Saharan Africa (SSA). We report here an academic partnership that commenced in 2003 between a US institution and six universities in SSA. The partnership addresses the human resources development challenge in Africa by strengthening public health education and research capacity to improve population and reproductive health (PRH) outcomes in low-resource settings. The partnership's core activities focused on increasing access to quality education, strengthening health research capacity and translating scholarship and science into policy and practices. Partnership programmes focused on the educational dimension of the human resources equation provide students with improved learning facilities and enhanced work environments and also provide faculty with opportunities for professional development and an enhanced capacity for curriculum delivery. By 2007, 48 faculty members from the six universities in SSA attended PRH courses at Johns Hopkins University, 93 PRH courses were offered across the six universities, 625 of their master's students elected PRHconcentrations and 158 had graduated. With the graduation of these and future student cohorts, the universities in SSA will systematically be expanding the number of public health practitioners and strengthening programme effectiveness to resolve reproductive health needs. Some challenges facing the partnership are described in this article. © 2010 Taylor & Francis.
Keywords: EMTREE medical terms: Africa; article; health care policy; health education; health service; human; medical education; medical research; medical student; priority journal; professional development; reproductive health; social change; MeSH: Africa South of the Sahara; Cooperative Behavior; Health Promotion; Humans; Program Development; Public Health; Reproductive Medicine; Staff Development; Universities